SYNTHESIS AND CHARACTERIZATION BY INFRARED AND MOSSBAUER SPECTROSCOPIES OF SOME NEW SnR2 (R = Me, Ph, Bu) RESIDUE CONTAINING ARBOXYALKYLPHOSPHONATE ADDUCTS AND DERIVATIVES - MOUHAMADOU SEMBENE BOYE; MOUHAMADOU BIRAME DIOP; MODOU SARR; AMINATA DIASSE-SARR; LIBASSE DIOP; ALAIN WATTIAUX (Journal of Engineering Studies and Research)
Four new carboxyalkylphosphonate SnR2 residue (R = Me, Ph, Bu) containing adducts and derivatives i.e. {(Cy2NH2)3(O2CCH2PO3)(SnBu2Cl2)} (1), {[(SnMe2Cl)(O2CCH2PO3H2)]4[Cy2NH2Cl]} (2), {(Me4N)(SnPh2Cl)[O2C(CH2)2 PO3H](SnPh2)[O2C(CH2)2PO3H]} (3) and {(Cy2NH2)2(O2CCH2PO3H)(SnPh2Cl2)2} (4), have been synthesized from one-pot reactions carried out in solution. All compounds have been investigated by spectral techniques (infrared and Mossbauer). The spectral studies have evidenced presence of several characteristic bands, especially υ (C=O), υ (OH), υ (CO2–), υ (PO32–) vibrations coming from carboxyalkylphosphonate ions, with wide absorption due to the NH2 groups coming from the dicyclohexylammonium counter ion (for 1, 2 and 4) and the intense doublet which show the presence of phenyl groups (for 3 and 4). In the solid state, the proposed structures are discrete or of infinite chain however hydrogen bonding patterns may occur. Event in this investigation is the presence, for compound 3, of two types of arrangement at Sn centers viz. an octahedron and a trigonal bipyramidal whose presence are ascertained by the Mossbauer parameters. The neutral or acidic carboxyalkylphosphonate ions exhibit a diversity of coordination behavior towards the Sn atoms: monochelating (carboxylate and phosphonate O-donor), monochelating through the carboxylate and unidentate coordinating O-donor through the phosphonic acid or acidic phosphonate, bichelating with chelations from carboxylate and acidic phosphonate, and unidentate from both the carboxylate and phosphonic acid